Effects of fibroblast growth factor 2 on muscle precursor cells from mouse limb and extraocular muscle - Austin J. Winker; Laura L. Johnson; Ria Jadhav; Catherine Nguyen; Elizabeth Hitch; Linda K. McLoon (PLoS ONE, 2026)
Fibroblast growth factor 2 (FGF2) is known to play a role in skeletal muscle development and growth. We examined two populations of myogenic precursor cells for their responses to FGF2 in vitro using both extraocular and limb skeletal muscle. Fluorescence-activated cell sorting (FACS) was used to isolate two different populations of myogenic precursor cells, the EECD34 cells (positive for CD34, and negative for Sca1, CD31, and CD45) and PAX7-positive cells, from tibialis anterior and extraocular muscles of mice. These cells were cultured and treated with either proliferation or differentiation media in the absence or the presence of FGF2, followed by assays to determine the effects on proliferation and differentiation. EECD34 cells and PAX7-positive cells from both muscles responded to FGF2 with significantly increased proliferation. Both myogenic precursor cell populations from each muscle type showed increased percentage of desmin-positive mononucleated cells, but decreased rates of fusion into multinucleated myotubes in the presence of FGF2 in this in vitro system relative to control cells. FGF2 has pleiotropic effects on skeletal muscles. Contrary to the literature, FGF2 did not inhibit differentiation, but did appear to decrease fusion into multinucleated myofibers in vitro . Examination of immunostaining for myomerger in differentiating PAX7-positive cells in the presence or absence of FGF2 demonstrated a significant reduction of expression in the presence of elevated FGF2 levels. These results provide a potential mechanism for reduction in myofiber number and size in the extraocular muscles in individuals with Apert syndrome, where FGF receptor 2 mutations maintain the receptor in an activated state resulting in significantly reduced myofiber size.